Polymer-assisted hydrothermal synthesis of Bi2S3 nanostructured flowers - Pilapong C. (2014)
Nanostructured Bi2S3 was hydrothermally produced from Bi2O3 and thiocarbohydrazide in acidic solutions containing PVA, PEG and PVP. By using XRD, SAED and Raman spectrometry, the products were orthorhombic Bi2S3, with four vibration modes at 139.6, 253.7, 310 and 968.9 cm-1. The phase was also in accordance with the diffraction patterns obtained by simulation. SEM, TEM and HRTEM show that the products are clusters of nanorods produced in polymer-free solution, and nanostructured flowers of nanospears, nanorods and nanoplates in the respective PVA-, PEG- and PVP-added solutions, with their growths in the same direction of [0 0 1]. A formation mechanism was also proposed according to their phase and morphologies. © 2009 Elsevier Ltd. All rights reserved.